Klimatologie der atmosphärischen Störungen über Europa - Dammann, Walter (ERDKUNDE, 1960)
This investigation using early as well as recent papers and publications as a starting point is based on the distribution of low pressure areas during the decade 1948?1959. Their distribution pattern was derived by counting them in 5° graticule fields as well as in relation to land and water surfaces and mountains. The pattern shows a surprisingly close connexion with the outlines of the European continent since, on the whole, the sea areas have larger and the land areas smaller frequency values. This result can be readily understood in terms of physical causation, viz differences in surface friction and temperature regime of land and water surfaces. The smaller surface friction over the sea compared with the land is relatively cyclogenic; this tendency is reinforced especially in winter by the thermal contrast between the air bodies on either side of the coastline. The reason why their effect comes out so clearly in the distribution pattern of the low pressure areas seems to be that pressure reacts most sensitively to those influences, at least when they combine. Thus the distribution pattern of the high altitude depressions in the 500 mb surface is very similar to that at ground level, an indication that these are genuine atmospheric disturbances. During the summer shallow thermal lows dominate the ground level pressure fields, especially above the land and during the day. Since they are formed within one and the same air mass they are rarely connected with frontal systems. They give, nevertheless, rise to a summerly monsoonal component of air exchange and a diurnal land-sea breeze, circulations whose intensity within the air pressure field increases with decreasing latitude (i. e. increasing temperature). The annual pattern of the frequency of deep (genuine) cyclones and the shallow low pressure formations in the North Sea and Baltic Sea regions, the middle European land mass and the Mediterranean regions, provide a basis for an understanding of the sequence of weather conditions from a synoptic-climatological starting point. The annual pattern of occurrence of high altitude depressions as compared with that at ground level shows no principal difference, except that their number is smaller at the 500 mb level. This lessening in intensity at a higher altitude is to be expected but the main reason for it is that the high temperature lows, and in winter the thermal highs, as formations of the air near the ground, do not reach up to this higher level. This also emerges from two specific examples of the major circulation of the atmosphere (summer heat-wave, winter frost spell). The result of this investigation shows that the sequence of weather conditions in Europe must not be seen merely as a consequence of atmospheric events of a higher order steered from afar (Atlantic Polar front). This sequence rather mirrors also local geographical influences, and does so to a degree which may not have been generally appreciated. These factors are not merely passive, there are thoroughly active ones as well. In particular the area near the coast makes itself felt with a kind of pseudo-permanent frontal zone en miniature which results from the differential friction and the contrast between maritime and continental air bodies, mentioned above, as a relative effect of the land-sea distribution. Mountain regions, on the other hand, have cyclone-repelling effects. The close link of the weather sequence with the earth’s surface shown and discussed in this paper through the distribution of low pressure areas provides a basis for making the seemingly haphazard and moody course of the weather (van Bebber, 1881) in its causes and appearance open to a truly geographical aspect more than has so far been possible.